Diet‐derived ergothioneine induces necroptosis in colorectal cancer cells by activating the SIRT3/MLKL pathway. Issue 10 (14th February 2022) - D'Onofrio, Nunzia; Martino, Elisa; Balestrieri, Anna; Mele, Luigi; Cautela, Domenico; Castaldo, Domenico; Balestrieri, Maria Luisa
Abstract : Ergothioneine (Egt) is a dietary amino acid which acts as an antioxidant to protect against ageing‐related diseases. We investigated the anti‐cancer properties of Egt in colorectal cancer cells (CRC). Egt treatment exerted cytotoxicity in a dose‐dependent manner, induced reactive oxygen species accumulation, loss of mitochondrial membrane potential and upregulation of the histone deacetylase SIRT3. Immunoblotting analysis indicated that the cell death occurred via necroptosis through activation of the RIP1/RIP3/MLKL pathway. An immunoprecipitation assay unveiled that the interaction between the terminal effector in necroptotic signalling MLKL and SIRT3 increased during the Egt treatment. SIRT3 gene silencing blocked the upregulation of MLKL and abolished the ability of Egt to induce necroptosis. The SIRT3–MLKL interaction may mediate the necroptotic effects of Egt in CRC, suggesting the potential of this dietary amino thione in the prevention of CRC. Abstract : Ergothioneine (Egt) is a diet‐derived amino acid with antioxidant properties present at particularly high levels in some foods. This in vitro study presents the first evidence for the role of dietary Egt in inducing necroptosis in colorectal cancer (CRC) cells, by oxidative stress generation and SIRT3 involvement, supporting its potential in the prevention of CRC.